Magnetic-Field-Enhanced H2S Sensitivity of Cu2O/NiO Heterostructure Ordered Nanoarrays - Sun, Haoming; Cao, Meng; Zhang, Pinhua; Tian, Xiaojing; Lu, Manli; Du, Lulu; Xue, Kaifeng; Cui, Guangliang (ACS sensors, 2022)
Magnetism is a promising external intervention for gas sensitivity based on a heterogeneous interfacial structure caused by the regulation of the heterogeneous interface conductivity and the surface oxygen adsorption. In this study, Cu2O/NiO heterostructure-ordered nanoarrays were prepared with a two-dimensional (2D) electrodeposition in situ assembly method for H2S gas detection at room temperature under the action of a magnetic field. The nanoarrays were multibarrier structures with a strictly periodic structure that was greater than hundreds of microns in size. The experimental data confirmed that the response of 50 ppm of H2S based on the nanoarrays was improved by nearly 61% with a relatively weak magnetic field. Particularly at a low concentration (≤20 ppm), the effect of the magnetic field enhancement on the sensitivity was more obvious. We attributed the enhancement of the gas sensitivity with the magnetic field to the regulation of the Cu2O–NiO interface conductance and the surface oxygen adsorption. This study demonstrated that a magnetic field could significantly enhance the gas sensitivity based on heterostructures. Results of this study provide an important reference for the application of magnetism in gas detection and the design of new gas-sensitive materials.